Perancangan Sistem Informasi Penerimaan Mahasiswa Baru Di STT Cipasung - Ubaidillah; Muhammad Rizky Munggaran; Alwi L. Amrillah; Sinta S. N; Azky Ali N (Cipasung Techno Pesantren: Jurnal Ilmiah, 2022)
Cipasung College of Technology (STT Cipasung) is one of the formal higher education institutions in the Cipasung Islamic Boarding School, Singaparna, Tasikmalaya, West Java. Cipasung Islamic Boarding School was founded in 1931 by the late KH. Ruhiat, located in the village of Cipakat, Singaparna District, Tasikmalaya Regency, about 100 km from the city of Bandung. From the results of interviews at the Cipasung College of Technology (STTC), PMB activities have used the Google form application which is then processed manually and has not been integrated into the information system (STTC). So that there are many new student data input data that are duplicated because there are input data that is more than once and also results in the data being a lot in common. In addition, staff work becomes less effective. Because staff have to check regularly and compare between existing duplicate data. And the PMB system that is implemented now has not been able to achieve the goal of what is expected to make it easier for the PMB Committee to validate PMB Participant data. Therefore it is necessary to design an information system improvement that can increase the effectiveness and efficiency of the PMB Committee. The design of the information system is the development of a new system from the existing old system, where problems that occur in the old system are expected to be resolved in the new system. designing a new student admissions information system that is suitable for solving problems that occur at STTC. The method that will be used in this study is the System Development Life Cycle method.